Solid-phase extraction followed by liquid chromatography quadrupole time-of-flight tandem mass spectrometry for the selective determination of fungicides in wine samples - Fontana, Ariel Ramón (2011)
In this work, a reliable and selective procedure for the determination of thirteen fungicides in red and white wine samples is proposed. Solid-phase extraction (SPE) and liquid chromatography (LC) tandem mass spectrometry (MS/MS), based on a hybrid quadrupole time-of-flight (QTOF) system, were used as sample preparation and determination techniques, respectively. Extraction and purification of target analytes was carried out simultaneously by using a reversed-phase Oasis HLB (200 mg) SPE cartridge combined with acetonitrile as elution solvent. Fungicides were determined operating the electrospray source in the positive ionization mode, with MS/MS conditions adjusted to obtain at least two intense product ions per compound, or registering two transitions per species when a single product was noticed. High selective MS/MS chromatograms were extracted using a mass window of 20 ppms for each product ion. Considering external calibration as quantification technique, the overall recoveries (accuracy) of the procedure ranged between 81% and 114% for red and white wine samples (10-20 mL), spiked at different concentrations between 5 and 100 ng mL-1. Relative standard deviations of the above data stayed below 12% and the limits of quantification (LOQs) of the method, calculated for 10 mL of wine, varied between 0.1 ng mL-1 for cyprodinil (CYP) and 0.7 ng mL-1< for myclobutanil (MYC). The optimized method was applied to seventeen commercial wines produced in Spain and obtained from local supermarkets. Nine fungicides were determined, at levels above the LOQs of the method, in the above samples. The maximum concentrations and the highest occurrence frequencies corresponded to metalaxyl (MET) and iprovalicarb (IPR).